Variant Qirā’āt of Riyāh and Rīh: An Interpretive Analysis in Tafsīr Al-Qurtubī - Rafita Septi Cahyani (Jurnal test, 2026)
The diversity of qirā’āt (variant readings) in the Qur’an is not merely a linguistic phenomenon but a profound source of theological and semantic depth in Islamic exegesis. This study focuses on the differences in qirā’āt between the singular form rīh (wind) and the plural form riyāh (winds) and their impact on the interpretation of wind-related verses in Tafsīr al-Qurṭubī. Using a qualitative, library-based approach, this research compiles Qur’anic verses concerning wind, identifies the contextual meaning of each term within its verse, explains the qirā’āt variations in the respective verses, and analyzes four key verses that demonstrate significant reading variants: al-Hijr: 22, al-Kahf: 45, Yūnus: 22, and Āli ‘Imrān: 117. The findings indicate that the singular form rīh is predominantly associated with contexts of punishment and destructive force, whereas the plural form riyāh generally appears in contexts of mercy and blessing. In his exegesis, al-Qurṭubī presents the diverse qirā’āt transmitted from various imams and elaborates on their semantic and thematic influence on the meaning of the verses. This study affirms that the differences in qirā’āt not only broaden interpretative possibilities but juga deepen the theological understanding of Qur’anic values. Moreover, this research fills a gap in existing scholarship by specifically addressing this theme within the framework of Tafsīr al-Qurṭubī.